Histopathological and Ultrastructure Implication of Calcium Nanoparticles in Wistar Rats - kandpal, Diksha; Chauhan, Ram Swaroop (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was conducted to observe the histopathological and ultrastructure alteration of the cell organelle if any using calcium nanoparticles (80 nm) in 35 Wistar rats. Calcium nanoparticles was administered at dose of 1000 mg/kg body weight in test group (G2, n=20) and control group (G1, n=15) providing them ad-libtum feed and water.The dose rate selected was a no observed adverse effect level (NOAEL) dose, apparently possessing no harm to the visceral organs. However, over a period of 90 days the calcium nanoparticle was suggestive of producing cytotoxic actions on liver, kidneys and spleen. To assess the effect of calcium nanoparticles, tissue samples were taken from rats at every 30 days interval and were subjected to histopathological procedures to observe the alteration induced by calcium nanoparticles. Subsequently, transmission electron microscopy (TEM) was also carried for the tissue samples to record the ultrastructure alterations associated with calcium nanoparticle administration. The histopathological and TEM showed the cytotoxic effect of nano calcium on the visceral organs. Therefore, the application of nanocalcium in biomedical sciences should be strictly regulated depending on the size of the nanoparticles used.
Keywords: Calcium; Histopathology; Nanoparticles; Transmission Electron Microscopy